The Gricean Model A Revising Rubric - Lovejoy, Kim Brian ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
H.P. Grice's theory of conversation can be used effectively to teach revision in composition courses because it teaches students the rules for effective writing. Grice has formulated a general principle, the Cooperative Principle, based on the assumption that talk-exchanges among speakers are "cooperative efforts" having "a common purpose or set of purposes." In observing the cooperative principle, four conversational maxims are also observed: (1) quantity--making as informative a contribution as required but not more so; (2) quality--saying only what is true and not including things for which there is insufficient evidence; (3) relation--being relevant; and (4) manner--avoiding obscurity, ambiguity, unnecessary prolixity, and disorder. The value of the Gricean model is that it asks new questions concerning revision and makes the standard questions clearer, more comprehensible, and more forceful by providing the students with an organizational scheme that does not sacrifice its heuristic power of simplicity. (EL)
ERIC Note: Paper presented at the Annual Meeting of the Conference on College Composition and Communication (36th, Minneapolis, MN, March 21-23, 1985).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Skills; Higher Education; Language Processing; Models; Revision (Written Composition); Verbal Communication; Writing (Composition); Writing Instruction; Writing Skills; Grice (HP); Opinion Papers; Speeches/Meeting Papers